2011
DOI: 10.1253/circj.cj-10-1029
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of the S.M.A.R.T. ControlTM Stent for Superficial Femoral Artery Lesions, J-SMART Registry

Abstract: Background:The use of a stent in the treatment of lesions of the superficial femoral artery (SFA) remains controversial. Although some reports have suggested that use of a nitinol stent in conjunction with aggressive medical management is effective for long SFA lesions, few long-term, large-scale studies have been done. Methods and Results:A retrospective analysis was conducted of data from a multicenter study in which the S.M.A.R.T. Control™ stent was used for treatment of de novo SFA lesions. A total of 528 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 21 publications
4
61
4
Order By: Relevance
“…6 Female gender, younger age, diabetes mellitus, no cilostazol, CLI, CTO, TASC II C/D lesion, and stent fracture have been associated with restenosis following nitinol stenting in the SFA. [16][17][18] In this study, female gender and TASC II C/D lesion were more prevalent in the TLR group compared to the no-TLR group on univariate analysis, but age, diabetes mellitus, use of cilostazol, CLI, and CTO were similar between the 2 groups. Previous studies reported that use of cilostazol pre-(25%) were detected on angiogram.…”
Section: Ivus Findingsmentioning
confidence: 52%
“…6 Female gender, younger age, diabetes mellitus, no cilostazol, CLI, CTO, TASC II C/D lesion, and stent fracture have been associated with restenosis following nitinol stenting in the SFA. [16][17][18] In this study, female gender and TASC II C/D lesion were more prevalent in the TLR group compared to the no-TLR group on univariate analysis, but age, diabetes mellitus, use of cilostazol, CLI, and CTO were similar between the 2 groups. Previous studies reported that use of cilostazol pre-(25%) were detected on angiogram.…”
Section: Ivus Findingsmentioning
confidence: 52%
“…In several studies, female gender was identifi ed as an independent risk factor for restenosis in the superfi cial femoral artery (SFA) after stent implantation [10,11]. This may correlate to the fi nding that female patients have a worse outcome regarding amputation and survival in the study of Kashyap et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, since it has been recently reported that device and technical developments provide high recanalization rates 3) . Comparing with F -P bypass, in a recent report 1) , the Fig.…”
Section: Discussionmentioning
confidence: 99%